The Effect of Baby Masange on the Quality of Sleep in Babies at TPMB Faulia Isnanda Feramita, Amd.Keb: pijat bayi - Wijaya, Dhinda Ayu; Fatayah, Elsa (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Infancy is a golden period for the growth and development of babies, so special attention needs to be paid to the baby's growth and development, especially on the baby's sleep pattern. Sleep is one form of baby's adaptation to their environment. But the problem is that babies find it very difficult to sleep at night and if not treated seriously there can be behavioral disorders, growth and development and brain disorders. Sleep disorders in babies can be overcome by doing baby massage. Baby massage is part of how to care for babies to grow and develop optimally. Baby massage is touch after birth, and can guarantee continuous body contact that can maintain a comfortable feeling for the baby.